FEMINISM OF ALICE PAUL IN IRON JAWED ANGELS MOVIE - Firdha Rachman; Imam Safrudi (LPPM Universitas Bina Sarana Informatika, 2014)
Most of women in the world are lack support for fundamental functions of a human life. They are less well nourished than men, less healthy, more vulnerable to physical violence and sexual abuse. They are much less likely than men to be literate, and still less likely to have professional or technical education. The objectives of this analysis are: (1) to know the characterization of Alice Paul as the main Character in Iron Jawed Angels Movie. (2) to find out the type of feminism in the main character. The method used is descriptive qualitative method and library research to collect the data and theories. The result of this thesis indicated that Alice has some great characterization such as smart, independent, brave, a great motivator, and educated woman. The type of her feminism in the main character is Liberal Feminism.